2019
DOI: 10.1108/pr-10-2018-0434
|View full text |Cite
|
Sign up to set email alerts
|

The role of teachers’ self-efficacy between trust and organisational citizenship behaviour among secondary school teachers

Abstract: Purpose The purpose of this paper is to examine the effects of teachers’ perception on trust over their willingness to exercise organisational citizenship behaviours (OCB) using self-efficacy as a mediator. Design/methodology/approach Usable questionnaires were collected from 411 teachers in secondary schools. A two-stage analytic approach was used to analyse the data. Findings The results indicated that trust and teachers’ self-efficacy dimensions (general teaching and personal teaching) are positively re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 86 publications
9
17
1
Order By: Relevance
“…In the same way, Somech and her colleagues (Bogler & Somech, 2004;Somech & Drach-Zahavy, 2000a) found that teachers with high self-efficacy displayed high levels of OCBs toward their colleagues and the organization. A very recent study conducted by Choong et al(2019) among 411 teachers in secondary schools indicated that teachers' self-efficacy dimensionsgeneral teaching and personal teaching -are positively related to OCB.…”
Section: Teachers' Self-efficacymentioning
confidence: 99%
“…In the same way, Somech and her colleagues (Bogler & Somech, 2004;Somech & Drach-Zahavy, 2000a) found that teachers with high self-efficacy displayed high levels of OCBs toward their colleagues and the organization. A very recent study conducted by Choong et al(2019) among 411 teachers in secondary schools indicated that teachers' self-efficacy dimensionsgeneral teaching and personal teaching -are positively related to OCB.…”
Section: Teachers' Self-efficacymentioning
confidence: 99%
“…
Organisational citizenship behaviour entails the display of voluntary extra-role behaviours that are not formally paid for but are essential for organisational success (Katz, 1964;Organ, 1988). Generally, OCB has been found to be related to teacher efficacy and workplace spirituality (Choong, Ng, Ai Na, & Tan, 2019;Mahipalan & Muhammed, 2019) and reduced turnover intention (Risa & Purba, 2019). It has also been reported that OCB predicts quality, creativity and efficient performance (Yaakobi & Weisberg, 2020).
…”
mentioning
confidence: 99%
“…Trust can be defined as “ A psychological condition characterized by the goal of tolerating vulnerability based on favorable expectations of another's intentions or behavior .” (Rousseau et al, 1998 , p. 395; Ali and Zafar, 2021 ). Trust in the leader has been an important area for research studies and has been studied concerning job antecedents and work outcomes (DeConinck, 2011 ), for example, Organizational citizenship behavior (Choong et al, 2019 ; Ayub et al, 2021a , b ), organizational commitment (Abbas et al, 2021 ), job satisfaction (Fard and Karimi, 2015 ), job performance (Zhu et al, 2021 ), and proactive behavior (Parker et al, 2006 ).…”
Section: Literature Reviewmentioning
confidence: 99%